2004
DOI: 10.1038/oby.2004.68
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Conjugated Linoleic Acid Isomers on Body Fat Mass in Overweight Humans

Abstract: MALPUECH-BRUGÈ RE, CORINNE, WILHELMINE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 27 publications
(83 reference statements)
2
69
1
3
Order By: Relevance
“…The present study corroborates previous ones using either the CLA mixture [2][3][4][5]7,9,10,13,14,19,[30][31][32] or either one of the two main isomers 33,34 demonstrating that fasting insulin and glucose do not change during supplementation. The CLA doses in these studies ranged from 0.6 to 6.8 g/day for time periods ranging from 5 days to 2 years in healthy, overweight or obese individuals.…”
Section: Discussionsupporting
confidence: 92%
“…The present study corroborates previous ones using either the CLA mixture [2][3][4][5]7,9,10,13,14,19,[30][31][32] or either one of the two main isomers 33,34 demonstrating that fasting insulin and glucose do not change during supplementation. The CLA doses in these studies ranged from 0.6 to 6.8 g/day for time periods ranging from 5 days to 2 years in healthy, overweight or obese individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Of six recent studies including similar measures of liver function, only Gaullier et al 10,11 showed significant within-group increases in AST. [8][9][10][11]13,29 However, this increase in AST was not significantly different from the control group and was not accompanied by changes in ALT or bilirubin. 10,11 Malpuech et al 29 measured liver size by ultrasound and concluded that CLA had no effect on liver ultrastructure or morphology and no evidence of hepatic lipodystrophy.…”
mentioning
confidence: 65%
“…In fact, the DXA method has been frequently used in development of functional foods or drugs. [24][25][26] Our previous data indicated that the sum of body fat mass, lean body mass, and bone mineral density measured by DXA was highly correlated with the body weight measured on a scale suggesting that the DXA method is applicable to measure these three components of the body. We therefore used DXA to investigate which of these three components contributed to the reduction of body weight.…”
Section: Discussionmentioning
confidence: 99%